Musyrifah in Increasing the Effectiveness of Learning in PESMA (Pesantren Mahasiswa) - Marniwati; Afiful Ikhwan; Muhibuddin Fadhli (NAJAHA, 2025)
This article discusses the role of musyrifah in increasing the learning effectiveness of students at PESMA Al Manar, Muhamadiyah University, Ponorogo. Aims to determine the effectiveness of musyrifah in managing learning programs implemented by the Al Manar Student Islamic Boarding School (Pesma). The problems in this research are as follows: 1) How is the effectiveness of learning applied by musyrifah 2) What are the steps by musyrifah to increase learning effectiveness. The type of research used is descriptive qualitative research. Data sources are obtained from primary and secondary data that are relevant to the problem being studied, data collection techniques include observation and interviews. Based on the results of research conducted at Pesma Al Manar, students who enter the Pesma Al Manar environment have an increase in the quality of learning, students can manage their study time well, and this cannot be separated from the role of Musyrif who guides them, Musyrifah helps students in increasing learning effectiveness which can also develop the learning system at Pesma Al Manar so that it is better and more developed.